The Climate Imperative of the 21st Century: Mobilising Youth Awareness and Action Amidst Global Warming (International Journal of Food and Nutritional Sciences, 2023)
the 21 st century is also experiencing one of the most threatening issues in history of human generation, that is, climate change. the issue has come out with far reaching consequences on international governance and intergenerational justice. The evidence of the increasing speed of global warming has achieved scientific consensus in recent years, although there is a disproportion in social awareness and activeness of politically activists. The younger generations, who will take most of the impact of the long-term effects of climate action are yet on the passive end of awareness. As it is depicted in this paper, youth awareness is crucial and can be used to deal with the climatic crisis that is being experienced today. Global climate governance is not a passive stakeholder but a critical actor of the young generations. The paper uses a conceptual and analytical approach to understand the structural and informational gap, which prevents successful engagement with the youth and assess the global initiatives to mobilise their efforts. The thesis that the scope of the current paper argues against is that the global response to climate without permanent actions to increase climate literacy and institutionalize the voices of youth will not be sufficient. This paper aims to make a contribution to larger discussions on climate governance and sustainability by making the engagement of youth to be viewed as a normative and political requirement.